Human metapneumovirus driven IFN-β production antagonizes macrophage transcriptional induction of IL1-β in response to bacterial pathogens - Loevenich, Simon; Montaldo, Nicola P.; Wickenhagen, Arthur; Sherstova, Tatyana; van Loon, Barbara; Boyartchuk, Victor; Anthonsen, Marit W. (Frontiers in Immunology, 2023)
Human metapneumovirus (HMPV) is a pneumovirus that may cause severe respiratory disease in humans. HMPV infection has been found to increase susceptibility to bacterial superinfections leading to increased morbidity and mortality. The molecular mechanisms underlying HMPV-mediated increase in bacterial susceptibility are poorly understood and largely understudied. Type I interferons (IFNs), while critical for antiviral defenses, may often have detrimental effects by skewing the host immune response and cytokine output of immune cells. It is currently unknown if HMPV skews the inflammatory response in human macrophages triggered by bacterial stimuli. Here we report that HMPV pre-infection impacts production of specific cytokines. HMPV strongly suppresses IL-1β transcription in response to LPS or heat-killed Pseudomonas aeruginosa and Streptococcus pneumonia, while enhancing mRNA levels of IL-6, TNF-α and IFN-. We demonstrate that in human macrophages the HMPV-mediated suppression of IL-1β transcription requires TANK-binding kinase 1 (TBK1) and signaling via the IFN--IFNAR axis. Interestingly, our results show that HMPV pre-infection did not impair the LPS-stimulated activation of NF-κB and HIF-1α, transcription factors that stimulate IL-1β mRNA synthesis in human cells. Furthermore, we determined that sequential HMPV-LPS treatment resulted in accumulation of the repressive epigenetic mark H3K27me3 at the IL1B promoter. Thus, for the first time we present data revealing the molecular mechanisms by which HMPV shapes the cytokine output of human macrophages exposed to bacterial pathogens/LPS, which appears to be dependent on epigenetic reprogramming at the IL1B promoter leading to reduced synthesis of IL-1β. These results may improve current understanding of the role of type I IFNs in respiratory disease mediated not only by HMPV, but also by other respiratory viruses that are associated with superinfections.